Testing the synteny of genes in Yponomeuta evonymella - Běhálková, Veronika (Jihočeská univerzita, 2020)
The aim of this thesis was to create a physical map of the bird-cherry ermine, Yponomeuta evonymella, chromosome Z1 and chromosome 15 using BAC-FISH mapping. The synteny of genes was compared to the closest outgroup of Yponomeuta spp., Plutella xylostella, in order to determine whether the P. xylostella genome sequence could be used as reference in reference-assissted genome assembly of Yponomeuta spp.
Testing the synteny of genes in Yponomeuta evonymella
Keywords: Yponomeuta evonymella; synteny of genes; BAC-FISH; chromosome Z; chromosome 15; Yponomeuta evonymella; synteny of genes; BAC-FISH; chromosome Z; chromosome 15